Web-based assessment tool for Teachers Digital Competency - Idrizi, Ermira; Kulakov, Andrea; Filiposka, Sonja; Trajkovikj, Vladimir (“St Kliment Ohridski” University-Bitola, Faculty of Information and Communication Technologies-Bitola, Republic of Macedonia, 2018)
Even though there are several different frameworks and standards for proving the digital competencies expected from teachers, there is a need for a Web-based assessment tools that allow real, dependable and valid assessment of these competencies. This paper addresses the design challenges related to a software solution for selfand peer-assessment of teachers’ digital competencies. In this system the competencies are assessed by a teacher his/her-self or by her/his peers using the performance indicators that are based on the competency model for Teachers.
Keywords: Teachers digital competencies, Web-based assessment tool